2021
DOI: 10.1177/10820132211025133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and particle size on physicochemical and techno-functional properties of peach palm peel flour (Bactris gasipaes, red and yellow ecotypes)

Abstract: In this study, the effect of temperature and particle size on the techno-functional properties of the flour from peach palm fruit peels ( Bactris gasipaes, red and yellow ecotype) were evaluated. The flour from peach palm epicarp obtained by natural convective drying was physicochemically characterized, including the assessment of total dietary fiber determined under the gravimetric enzymatic method. The results obtained showed that temperature and particle size present a significant effect ( p < 0.001) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In this study, a significant Pearson correlation coefficient (r = 0.6022, p = 0.001) between WHC and PY was observed (Table S3), indicating that WHC is notably influenced by the presence of uronic acid groups [47]. Considering that pectin is part of soluble fibre, Martínez-Girón et al [48] supported this correlation by reporting an increase in water absorption capacity in red and yellow peach palm peels when reducing PS from 0.25 to 0.105 mm. According to Zhuang et al [29] and Mai et al [25], the finer the particle size, the better the water interaction with hydroxyl (-OH) groups [25].…”
Section: Techno-functional and Physicochemical Properties Of Rdf-ppsupporting
confidence: 51%
See 2 more Smart Citations
“…In this study, a significant Pearson correlation coefficient (r = 0.6022, p = 0.001) between WHC and PY was observed (Table S3), indicating that WHC is notably influenced by the presence of uronic acid groups [47]. Considering that pectin is part of soluble fibre, Martínez-Girón et al [48] supported this correlation by reporting an increase in water absorption capacity in red and yellow peach palm peels when reducing PS from 0.25 to 0.105 mm. According to Zhuang et al [29] and Mai et al [25], the finer the particle size, the better the water interaction with hydroxyl (-OH) groups [25].…”
Section: Techno-functional and Physicochemical Properties Of Rdf-ppsupporting
confidence: 51%
“…Similar results were obtained by Mai et al [25] and Zhuang et al [29] when PS was reduced in HU peels. According to Ahmed et al [41], Martínez-Girón et al [48], Tejada-Ortigoza et al [47], and Zlatanović et al [49], an increase in OHC is attributed to the structural composition, surface properties, and overall charge density of fibres. In our study, the observed increase in OHC at the finest PS may be attributed to the occurring capillary attraction facilitated by the physical retention of oil in honeycomb-like compartments of RDF-PP resulting from the milling process [25,48].…”
Section: Techno-functional and Physicochemical Properties Of Rdf-ppmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez‐Girón et al . (2021) revealed a considerable rise in WAI and WSI as particle size decreased in peach palm peel flours. Variations in WAI are caused by different types of hydrophilic carbohydrates and protein structures found in the samples.…”
Section: Resultsmentioning
confidence: 97%
“…Similar results were obtained by Mai et al [25] and Zhuang et al [28] when PS was reduced in HU peels. According to Ahmed et al [40], Martínez-Girón et al [51], Tejada-Ortigoza et al [46], and Zlatanović et al [47], an increase in OHC is attributed to the structural composition, surface properties, and overall charge density of fibres. In our study, the increase in OHC at the finest PS may be explained by the reduced amount of hydroxyl groups in RDF-PP, which led to an increased hydrophobic capacity [25].…”
Section: Techno-functional and Physicochemical Properties Of Rdf-ppmentioning
confidence: 99%